Jenis-Jenis Kupu-Kupu (Sub Ordo Rhopalocera) yang Terdapat di Kawasan Hapanasan, Kabupaten Rokan Hulu, Provinsi Riau - CHAHYADI, ENNIE; BIBAS, ELPE (Jurusan Biologi FMIPA Universitas Riau, 2016)
The objective of this study was to identify the diversity of butterfly (sub ordo Rhoplalocera) in Hapanasanpark, Riau Province. The study was conducted from January to February 2014. Imagos were collected inthe morning and afternoon. They were captured directly by using butterfly net. The result of this studyshowed that there were 48 Rhoplalocera butterfly species of 5 families, that consisted of Hesperidae (5species), Papilionidae (6 species), Pieridae (9 species), Nymphalidae (26 species), and Lycaenidae (2species). The most abundant species belongs to Nymphalidae family. In this study we found Troideshelena. This species is protected by. laws and recorded in Appendix II CITES.Key words : Butterflies, Rhopalocera, Hapanasan